Prokaryotic expression of a novel mouse pro-apoptosis protein PNAS-4 and application of its polyclonal antibodies - Zhang,P. (2008)
Mouse PNAS-4 (mPNAS-4) has 96% identity with human PNAS-4 (hPNAS-4) in primary sequence and has been reported to be involved in the apoptotic response to DNA damage. However, there have been no studies reported of the biological functions of mPNAS-4. In studies conducted by our group (unpublished data), it was interesting to note that overexpression of mPNAS-4 promoted apoptotic death in Lewis lung carcinoma cells (LL2) and colon carcinoma cells (CT26) of mice both in vitro and in vivo. In our studies, mPNAS-4 was cloned into the pGEX-6P-1 vector with GST tag at N-terminal in Escherichia coli strain BL21(DE3). The soluble and insoluble expression of recombinant protein mPNAS-4 (rmPNAS-4) was temperature-dependent. The majority of rmPNAS-4 was insoluble at 37°C, while it was almost exclusively expressed in soluble form at 20°C. The soluble rmPNAS-4 was purified by one-step affinity purification, using a glutathione Sepharose 4B column. The rmPNAS-4 protein was further identified by electrospray ionization-mass spectrometry analysis. The search parameters of the parent and fragment mass error tolerance were set at 0.1 and 0.05 kDa, respectively, and the sequence coverage of search result was 28%. The purified rmPNAS-4 was further used as immunogen to raise polyclonal antibodies in New Zealand white rabbit, which were suitable to detect both the recombinant and the endogenous mPNAS-4 in mouse brain tissue and LL2 cells after immunoblotting and/or immunostaining. The purified rmPNAS-4 and our prepared anti-mPNAS-4 polyclonal antibodies may provide useful tools for future biological function studies for mPNAS.